The Mind of a Leader A Christian Perspective of the Thoughts, Mental Models, and Perceptions That Shape Leadership Behavior - Winston, Bruce E. (Christian Faith Perspectives in Leadership and Business, 2022)
XIV, 244 p. 2 illus.